Physical geology - Plummer, Charles C. (McGraw-Hill, 2010)
This book provides a great frame of reference and perspective on the subject of Geology. It provides a well-structured overview of the subject, as well as a good guide for practical learning. It is an attractive book, and the content is surprisingly accessible, so it is suitable for a non-specialist audience as well as those studying it as a prescribed text